The Timing and Abundance of IL-2Rβ (CD122) Expression Control Thymic iNKT Cell Generation and NKT1 Subset Differentiation - Won, Hee Yeun; Kim, Hye Kyung; Crossman, Assiatu; Awasthi, Parirokh; Gress, Ronald E.; Park, Jung-Hyun (Frontiers in Immunology, 2021)
Invariant NKT (iNKT) cells are thymus-generated innate-like T cells, comprised of three distinct subsets with divergent effector functions. The molecular mechanism that drives the lineage trifurcation of immature iNKT cells into the NKT1, NKT2, and NKT17 subsets remains a controversial issue that remains to be resolved. Because cytokine receptor signaling is necessary for iNKT cell generation, cytokines are proposed to contribute to iNKT subset differentiation also. However, the precise roles and requirements of cytokines in these processes are not fully understood. Here, we show that IL-2Rb, a nonredundant component of the IL-15 receptor complex, plays a critical role in both the development and differentiation of thymic iNKT cells. While the induction of IL-2Rb expression on postselection thymocytes is necessary to drive the generation of iNKT cells, surprisingly, premature IL-2Rb expression on immature iNKT cells was detrimental to their development. Moreover, while IL-2Rb is necessary for NKT1 generation, paradoxically, we found that the increased abundance of IL-2Rb suppressed NKT1 generation without affecting NKT2 and NKT17 cell differentiation. Thus, the timing and abundance of IL-2Rb expression control iNKT lineage fate and development, thereby establishing cytokine receptor expression as a critical regulator of thymic iNKT cell differentiation.